13C/15N‐Enriched l‐Dopa as a Triple‐Resonance NMR Probe to Monitor Neurotransmitter Dopamine in the Brain and Liver Extracts of Mice. Issue 2 (30th December 2015) - Yamada, Hisatsugu; Kameda, Tetsuro; Kimura, Yu; Imai, Hirohiko; Matsuda, Tetsuya; Sando, Shinsuke; Toshimitsu, Akio; Aoyama, Yasuhiro; Kondo, Teruyuki
Abstract: In an attempt to monitor μm ‐level trace constituents, we applied here 1 H‐{ 13 C‐ 15 N} triple‐resonance nuclear magnetic resonance (NMR) to 13 C/ 15 N‐enrichedl ‐Dopa as the inevitable precursor of the neurotransmitter dopamine in the brain. The perfect selectivity (to render endogenous components silent) and μm ‐level sensitivity (700 MHz spectrometer equipped with a cryogenic probe) of triple‐resonance allowed the unambiguous and quantitative metabolic and pharmacokinetic analyses of administeredl ‐Dopa/dopamine in the brain and liver of mice. The level of dopamine generated in the brain (within the range 7–76 μm, which covers the typical stimulated level of ∼30 μm ) could be clearly monitored ex vivo, but was slightly short of the detection limit of a 7 T MR machine for small animals. This work suggests that μm ‐level trace constituents are potential targets of ex vivo monitoring as long as they contain N atom(s) and their appropriate 13 C/ 15 N‐enrichment is synthetically accessible. Abstract : Traces via triple resonance ! Tripleresonance high‐resolution NMR with a cryogenic probe at 16.4 T is sensitive and selective enough to perform quantitative metabolic/pharmacokinetic analysis ofl ‐Dopa/dopamine in brain and liver extracts from mice. This work suggests that μm ‐level trace constituents are potential targets of ex vivo monitoring as long as they contain N atoms and their appropriate 13 C/ 15 N‐enrichment is synthetically accessible.